The Impact of Organizational Excellence on Achieving Organizational Excellence: An Empirical Study in Branches of Traditional Private Banks in Lattakia City - متوج, على; سامر أحمد قاسم; جميل عيسى (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The aim of the research is to study the impact of organizational ambidexterity (exploration ambidexterity, exploitation ambidexterity) on achieving organizational excellence (leadership excellence, human resources excellence, service excellence) in branches of traditional private banks in Lattakia City. To achieve the research objectives, the researcher adopted the descriptive approach. The research community included all administrative employees in branches of traditional private commercial banks in Lattakia City. Using the comprehensive enumeration method, 60 questionnaires were distributed to all administrative employees, and 52 complete questionnaires were retrieved that were valid for statistical analysis, with a response rate of 86.67%. The research reached a set of results, the most important of which are: the existence of a strong positive effect with statistical significance of the dimensions of organizational ambidexterity (exploration ambidexterity, exploitation ambidexterity) on achieving organizational excellence related to the dimensions of leadership excellence and human resources excellence, while the positive effect was acceptable and statistically significant for the dimensions of organizational ambidexterity in achieving organizational excellence related to the service dimension.